Analysis of residential satisfaction in the conversion of Beijing’s stock buildings into rental housing - Xuefen Hu; Jian Suo; Ningbo Kou; Mengxue Wu; Shiyu Wang (Scientific Reports, 2024)
Abstract This paper investigates the residential satisfaction levels of tenants living in rental housing converted from non-residential stock buildings in Beijing. A stratified random sampling method was used to select 353 tenants from five apartments based on the plan form and location of the units for a structured questionnaire survey. The results of a hierarchical regression analysis indicated that subjective attributes were more influential in determining residential satisfaction than the objective physical and demographic attributes of the apartments. Within the five dimensions of subjective attributes, the "interior space" dimension had the greatest impact on predicting residential satisfaction. In addition, a one-way ANOVA analysis showed that the floor plan of the apartments also played a significant role in determining residential satisfaction, S-type and office park-type (Converted from an office park) layouts received the highest satisfaction ratings. This research provides valuable insights for revitalizing non-residential stock buildings and offers theoretical support for converting more non-residential stock buildings into rental housing in the future.